Features of dike magmatism in the Northern frame of the Pechenga structure - Terekhov, E. N.; Morozov, Yu. A.; Smolkin, V. F.; Bayanova, T. B.; Serov, P. A.; Shcherbakova, T. F.; Smulskaya, A. I. (Vestnik MGTU, 2019)
A comprehensive study of Paleoproterozoic dike complexes within North-Western part of the Kola region has been carried out. The research allows establish stages of their formation, correlate with thickness of volcanites and reconstruct the geodynamic conditions of introduction. The most common dikes are composed of quartz dolerites with U-Pb age 2304 ± 1 Ma, εNd = –1.12 and model Sm-Nd protolite age – 2838 Ma. Dikes from the Ambarnaya Bay area correlate to dike swarm of the village Liinakhamari. Rocks of both swarms are correlated with volcanogenic formations of andesibasalt composition, the lower part of Pechenga structure section. Small fluctuations MgO (4–7 wt.%), low Cr (10–50 ppm) and moderate Y, Zr, REE, weakly fractionated HREE with minor negative Eu anomaly and (La/Yb)n = 5.1–5.8 are typical for dolerites. Rocks are enriched by Rb, Ba, K, depleted by Nb, Ti, and have low Sr/Y = 11–13. Dikes of quartz dolerites break plagiogranites and granites of the Archean foundation. U-Pb age of plagiogranites is 2722 ± 4 Ma. Age of granites is younger – 2418 ± 8 Ma. Plagiogranite according to Sm-Nd analysis of its gross sample has εNd = +3.77, which is close to the values of depleted mantle and indicates the origin of the rock from depleted mantle source. Granite of xenoliths dikes of quartz dolerites is characterized by εNd = –0.36. This indicates formation of rocks from a source more enriched than CHUR reservoir. The model Sm-Nd age of the protolite is 2744 Ma. These data confirm the initiation of rifting of Paleoproterozoic Pechenga-Varzugskaya belt in the continental crust. The synchronous introduction of dike swarms of quartz dolerites with the eruption of andesibasalt volcanites is determined by their structural confinement in the regional part of the "dying" sumian plume and to region of dynamic influence of regional shear zones. Комплексное изучение палеопротерозойских дайковых комплексов в пределах северо-западной части Кольского региона позволило установить этапы их формирования, провести корреляцию с ...